(untitled) (Latakia University Journal -Basic Sciences Series, 2013)
يتضمن هذا العمل المفاهيم التالية: تعريف البولارون، المفاهيم الثانوية للبولارونات، بولارون كبير، بولارون صغير، تطوير النظرية الكمية للكمون الذاتي للإلكترون في جملة مؤلفة من تماس ثلاث طبقات رقيقة لأنصاف نواقل مختلفة،إيجاد الطاقة الكمونية للبولارون، ودراسة الحالة التي يكون فيها الإلكترون داخل الطبقة الرقيقة أو على سطحها. دراسة تأثير انزوتروبية العازلية الكهربائية للطبقات في عبارة الطاقة الكمونية للإلكترون (الثقب) في طبقة رقيقة. This paper contains the following concepts: definitions about polaron, concepts of polarons, large polaron, small polaron, and development of quantum theory for electron self-action potential in a system consisting of three contact different semi-conductor thin layers, finding polaron potential energy, and studying the case in which an electron is located inside the thin layer or on its surface. Studying the effect of dielectric anisotropy of layers on electron-(hole) potential energy in the above mentioned thin layers.